Bilateral Differential Topography—A Novel Topographic Algorithm for Keratoconus and Ectatic Disease Screening - Shen, Yang; Xian, Yiyong; Han, Tian; Wang, Xuanqi; Zhou, Xingtao (Frontiers in Bioengineering and Biotechnology, 2021)
Purpose: The purpose of this study was to establish a novel bilateral differential topographic algorithm and assess its efficacy for screening of keratoconus and corneal ectasia before corneal refractive surgery. Methods: One hundred and sixty-one consecutive patients (115 men and 46 women, aged 22.8±6.8 years) with keratoconus, including clinical keratoconus, subclinical keratoconus, forme fruste keratoconus (FFK), and corneal ectasia (KC group) and 174 consecutive patients (97 males and 77 females, aged 25.1±6.7 years) with ametropia (control group) at the Eye and ENT hospital of Fudan University from June 2018 to April 2021 were included. Bilateral differential keratometry, elevation, and pachymetry topographies were composed based on raw topographic data obtained by a Scheimpflug imaging anterior segment analyzer. Key bilateral differential characteristic parameters were calculated. SPSS 20 (SPSS Inc., IBM) was used for statistical analyses and the receiver operating characteristic (ROC) curves were used to determine the diagnostic efficacies. Results: Mann-Whitney tests detected that the front keratometry, front elevation, corneal pachymetry, and back elevation maximal, mean, and standard deviation values within a 1.5-mm radius of the bilateral differential topography were all significantly higher in the KC group than the control group (all P-values <0.001). The front keratometry mean (ΔFKmean) and standard deviation (ΔFKsd) and the front elevation maximal (ΔFEmax) and standard deviation (ΔFEsd) values within a 1.5-mm radius of the bilateral differential topography yielded the four highest accuracies (area under the receiver operating characteristic curve = 0.985, 0.985, 0.984, and 0.983, respectively) for discriminating KC cases (including FFK cases) from normal cases. Cut-off values of 0.75 diopters (D) for the ΔFKmean, 0.67 D for the ΔFKsd, 2.9 μm for the ΔFEsd, and 14.6 μm for the ΔFEmax had the highest sensitivities (95.7%, 95.0%, 96.9%, and 95.0%, respectively) and specificities (96.0%, 97.7%, 94.8%, and 95.4%, respectively). Conclusion: Bilateral differential topographic parameters are efficient for the early detection of keratoconus and corneal ectasia. This bilateral differential topographic algorithm may complement conventional diagnostic models by improving the sensitivity and specificity of screening for early keratoconus and ectasia before corneal refractive surgeries.